Prospecção de bioativos extracelulares de holobiontes fúngicos de macroalgas marinhas - Brito, Anna Luisa de Carvalho (2024)
Over the years, resistance to antibiotics has caused millions of deaths and severe economic losses on a global scale. Multisectoral efforts are thus warranted in order to curb the phenomenon of antimicrobial resistance, and it falls to scientific research to develop novel molecules designed to hold off the advancement of multiresistant microorganisms. Fungi are historically sources of molecules with biological activities, the first antibiotic known to humanity was created from fungal cells, and to this day, organisms from this kingdom are used as a source of bioactives. The interaction between species present in the microbiome and host organisms can influence the production and activity of these bioactives. Therefore, the aim of this work was to prospect for bioactives from fungi belonging to the microbiota of five species of marine macroalgae, and to characterize these fungi and the inhibitory potential of their produced bioactives. The inhibitory potential analysis was carried out via agar plug test, and was used in the production of organic extracts with ethyl acetate. These extracts had their inhibitory indices measured on MIC, MBC, and IC50. The extracts with the best inhibitory indexes had the producing fungi identified, and the composition of the extract analyzed by the UPLC system coupled to quadrupole mass detectors. 24 fungi were isolated, 11 exerted inhibition halos against five species of pathogenic standard strains, and were used in the production of fungal extracts. Six extracts exerted statistically significant inhibition against standard strains of E. coli and V. cholera. The E1 extract was considered to have the best inhibitory potential as it presented the lowest concentrations to exert an inhibitory effect. Inhibition only of Gram- negative microorganisms is an important factor in the development of antimicrobials with less potential for inducing bacterial resistance. Pensulfonoxy was identified in 5 out of the 6 inhibitory extracts, and has already been reported in the literature as a bioactive with antimicrobial capacity, and was therefore the probable compound causing the inhibition. The present study shows a variety of marine fungi that are still poor explored, and their potential as source of new antimicrobial molecules with actions directed at Gram-negative bacteria, which constitute a priority class to be dealt according to data from the World Health Organization.